Suggestions for prevention (Journal of Parents and Teachers, 2014)
Bullying is still an alarming social issue and concern for schools. This article explains the different types of bullying, the typical profile of a bully, a victim and an observer. In addition it suggests some activities to work with bullying and humiliation in class. Prevention is the best antidote to fight against it.
Keywords: values; bullying; bullying prevention; activity; role-playing.